Presepsin: Is it a New Biomarker for the Diagnosis and Management of Ventilator-Associated Pneumonia? - Enez, Murat; Ozer Balin, Safak; Telo, Selda; Cakmak, Erkan; Demirel, Ismail (Bilimsel Tip Yayinevi, 2024)
Introduction: Nowadays, the use of biomarkers is recommended to facilitate the diagnosis of ventilator-associated pneumonia. Although there is no specific biomarker for this condition, the most frequently studied biological tools have been procalcitonin, C-reactive protein (CRP), and myeloid cells type 1. Presepsin, a recently emerged molecule, is used as an early indicator of various infections. This study aimed to determine the role of presepsin in the diagnosis and treatment follow-up of ventilator-associated pneumonia. Materials and Methods: Blood samples were taken from the patients on the initial day of ventilator-associated pneumonia diagnosis and on the third and seventh days of treatment to determine the level of presepsin. Additionally, on the same days, venous blood was collected for complete blood count, erythrocyte sedimentation rate, procalcitonin, and CRP measurements. Demographic and microbiological data of the patients were obtained from our hospital's electronic record system. Results: Forty-two patients diagnosed with ventilator-associated pneumonia and 30 healthy volunteers were included in this study. The presepsin value on day zero, when ventilator-associated pneumonia was diagnosed, was 1.09 (0.05-10.5) ng/mL in the patient group and 0.21 (0.03-5.56) ng/mL in the control group (p <= 0.01). A positive correlation was observed between presepsin and procalcitonin on Day 0 in the patient group (p= 0.036), while a negative correlation was found between presepsin and CRP (p= 0.001). In 25 patients who responded to treatment (procalcitonin <= 1 ng/mL), a positive correlation was identified between presepsin and procalcitonin on the seventh day of treatment (p= 0.001). The cut-off value for predicting the diagnosis of ventilator-associated pneumonia was determined to be 0.537 ng/mL. Conclusion: Based on the data obtained from this study, presepsin can be considered an effective biomarker for both diagnosing and guiding the termination of treatment in patients with ventilator-associated pneumonia.
Keywords: Ventilator-associated pneumonia; Presepsin; Intensive care unit